First-Session Therapeutic Relationship and Outcome in High Risk Adolescents Intensive Group Psychotherapeutic Programme - Hauber, Kirsten; Boon, Albert (Frontiers in Psychology, 2022)
Background: An important determinant of therapy outcome is the quality of the therapeutic relationship. This study evaluated the association between the client’s assessment of first-session therapeutic relationship (FSTR) and outcome in an intensive MBT treatment for adolescents with personality disorders. Method: Patients (N = 92) were measured weekly during intensive MBT group treatment. The therapeutic relationship was measured with the Child version of the Session Rating Scale (C-SRS) that was completed after each group therapy session by the patient. Outcome was measures with the Child version of the Outcome Rating Scale (C-ORS). Reliable change index (RCI) was calculated for the both instruments to determine significant changes in therapeutic relationship and outcome. Results: A good FRST gave twice as much chance of a significantly better outcome. Especially for those with moderate FSTR, establishing and maintaining a good working relationship during treatment could increase the chances of a good outcome considerably. In contrast, adolescents with low FSTR had little chance of positive outcome regardless of any improvement in the therapeutic relationship. Conclusions: Adolescents assessment of FRST is indicative of the chance of a good outcome.